Investigating Tenor Variable and Interpersonal Meaning in Amma Darko’s the Housemaid - DADJO, Servais Dieu-Donné Yédia (My University, 2021)
This paper deals with tenor and interpersonal meaning in Amma Darko’s The Housemaid. For the completion of this paper, three (03) extracts have been selected from The Housemaid and the Systemic Functional Linguistics theory has been applied to each of them in order to analyse the linguistic features which connote interpersonal meaning in the selected extracts by describing how participants establish and maintain social relationships between themselves so as to have a deep understanding of the novel and provide a new interpretation of it. Both quantitative and qualitative methods have been used in this work. The study reveals that Darko overtly identifies herself as a spokeswoman for defenseless women. Indeed, by choosing women as protagonists, she aims at not only unveiling the detrimental effects of patriarchal societies in Africa, but also advocating for a society wherein exploitation and domination of men do not exist. It can thus be contended that the demolition of men’s domination over women, the feminism in Africa and african women’s difficult life conditions are the major messages conveyed through The Housemaid.
Keywords: Feminism; tenor; interpersonal meaning; Systemic Functional; Linguistics.